Comparative Genomics Analyses Support the Reclassification of Bisgaard Taxon 40 as Mergibacter gen. nov., With Mergibacter septicus sp. nov. as Type Species: Novel Insights Into the Phylogeny and Virulence Factors of a Pasteurellaceae Family Member Associated With Mortality Events in Seabirds - De Luca, Eliana; Álvarez-Narváez, Sonsiray; Maboni, Grazieli; Baptista, Rodrigo P.; Nemeth, Nicole M.; Niedringhaus, Kevin D.; Ladner, Jason T.; Lorch, Jeffrey M.; Koroleva, Galina; Lovett, Sean; Palacios, Gustavo F.; Sanchez, Susan (Frontiers in Microbiology, 2021)
The Pasteurellaceae family has been associated with fatal diseases in numerous avian species. Several new taxa within this family, including Bisgaard taxon 40, have been recently described in wild birds, but their genomic characteristics and pathogenicity are not well understood. We isolated Bisgaard taxon 40 from four species of seabirds, including one sampled during a mass, multi-species mortality event in Florida, USA. Here, we present a comprehensive phenotypic and genetic characterization of Bisgaard taxon 40 and comparative genomic analysis with reference strains from the Pasteurellaceae family, aiming at determining its phylogenetic position, antimicrobial susceptibility profile, and identifying putative virulence factors. In-silico multilocus sequence-based and whole-genome-based phylogenetic analysis clustered all Bisgaard taxon 40 strains together on a distinct branch separated from the other members of the Pasteurellaceae family, indicating that Bisgaard taxon 40 could represent a new genus. These findings were further supported by protein similarity analyses using the concatenation of 31 conserved proteins and other taxonomic approaches such as the percentage of conserved protein (POCP) test. Additionally, several putative virulence factors were identified, including those associated with adhesion (capsule, ompA, ompH)) and colonization (exbD, fur, galU, galE, lpxA, lpxC, and kdsA) of the host and a cytolethal distending toxin (cdt), which may have played a role in disease development leading to the mortality event. Considerably low minimum inhibitory concentrations (MICs) were found for all the drugs tested, in concordance with the absence of antimicrobial resistance genes in these genomes. The novel findings of this study highlight genomic and phenotypic characteristics of this bacterium, providing insights into genome evolution and pathogenicity. We propose a reclassification of these organisms within the Pasteurellaceae family, designated as Mergibacter gen. nov., with Mergibacter septicus sp. nov. as the type species. The type strain is Mergibacter septicus A25201 T (=DSM 112696).